2016
DOI: 10.5539/elt.v9n8p85
|View full text |Cite
|
Sign up to set email alerts
|

The Role of WhatsApp in Teaching Vocabulary to Iranian EFL Learners at Junior High School

Abstract: The availability and the use of mobile messaging applications are increasingly widespread among the new generation of students in Iran. The present study aimed to investigate the role of WhatsApp in the vocabulary learning improvement of Iranian junior high school EFL students. Using a mixed method design, a group of 60 students including 30 male and 30 female students studying at two male and female junior high schools in Isfahan, Iran participated in the study. A pre-test and post-test were used. Four Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 15 publications
(17 reference statements)
12
49
0
Order By: Relevance
“…Wang and Shih (2015) inferred that the experimental group who studied vocabulary through the mobile vocabulary learning application scored significantly higher than the control group who studied the same learning materials in paper-based format. In another study conducted by Jafari and Chalak (2016), four English classes were instructed, and the experimental group received vocabulary instructions electronically 4 days a week for 4 weeks using the WhatsApp whereas the control group was taught vocabularies of their textbook inside the classroom by traditional method. The results of the study revealed that using WhatsApp had significant role in vocabulary learning of the students.…”
Section: Results Related To Quantitative Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Wang and Shih (2015) inferred that the experimental group who studied vocabulary through the mobile vocabulary learning application scored significantly higher than the control group who studied the same learning materials in paper-based format. In another study conducted by Jafari and Chalak (2016), four English classes were instructed, and the experimental group received vocabulary instructions electronically 4 days a week for 4 weeks using the WhatsApp whereas the control group was taught vocabularies of their textbook inside the classroom by traditional method. The results of the study revealed that using WhatsApp had significant role in vocabulary learning of the students.…”
Section: Results Related To Quantitative Datamentioning
confidence: 99%
“…tional use of WhatsApp have indicated that it has potential to support learning anytime and anywhere, increase interest and motivation, provide cooperation, enhance learning, improve the interaction among learners, and learner-teacher (Bouhnik & Deshen, 2014;Church & de Oliveira, 2013;Guler, 2017;Jafari & Chalak, 2016;Mistar & Embi, 2016;Plana et al, 2013;Rambe & Bere, 2013;Rambe & Chipunza, 2013;Smit, 2012). Accordingly, it seems possible to suggest that Facebook and WhatsApp, along with their potential to provide informal cooperative learning environment, both could be more dynamic and effective with the help of Internet and mobile devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As mobile phones have become the norm in classrooms, instructors have sought to incorporate technology into the curriculum in meaningful ways (Blattner & Fiori, . For this reason, mobile messaging applications have attracted attention as a medium to foster the academic vocabulary because of their accessibility and power to connect learners past the classroom walls (Bensalem, ; Jafari & Chalak, ). It is, however, of great importance to approach technology incorporation with pedagogically sound language goals (Gonzáles‐Lloret & Ortega, ).…”
mentioning
confidence: 99%
“…Thus, in an effort to converge technology‐mediated practices while increasing vocabulary knowledge, lowering writing anxiety, and fostering motivation, I engaged students in the explicit practice of academic vocabulary through a WhatsApp chat group. WhatsApp research, though in its infancy, has shown potential for vocabulary acquisition (Bensalem, ; Jafari & Chalak, ). I asked the 13 EL students in my low‐intermediate writing class to think of this activity as a “vocabulary challenge” rather than a required assignment.…”
mentioning
confidence: 99%